2014
DOI: 10.1002/pros.22934
|View full text |Cite
|
Sign up to set email alerts
|

Prostatic angiogenic responses in late life: Antiangiogenic therapy influences and relation with the glandular microenvironment in the transgenic adenocarcinoma of mouse prostate (TRAMP) model

Abstract: Prostatic angiogenesis stimulation during senescence favored the development of neoplastic lesions, considering the pro-angiogenic microenvironment as a common aspect also observed during cancer progression in TRAMP mice. The combined antiangiogenic therapy was more efficient, leading to enhanced imbalance towards angiogenic inhibition in the organ. Finally, finasteride administration might secondarily upregulate the expression of pro-angiogenic factors, pointing to the harmful effects of this therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
5

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 74 publications
2
17
0
5
Order By: Relevance
“…Recently, two studies from our research group showed the effects of antiangiogenic therapy, where there was a decrease of microvessel density in TRAMP animals. In addition to this, there was also a reduction of tissue inflammation [26, 27]. However, it is known that there is an occurrence of a compensatory mechanism for signaling exchange between VEGF, PDGF and FGF pathways, as angiogenesis is regulated by multiple factors, resulting in tumor resistance to therapy which only inhibits VEGF [25, 28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, two studies from our research group showed the effects of antiangiogenic therapy, where there was a decrease of microvessel density in TRAMP animals. In addition to this, there was also a reduction of tissue inflammation [26, 27]. However, it is known that there is an occurrence of a compensatory mechanism for signaling exchange between VEGF, PDGF and FGF pathways, as angiogenesis is regulated by multiple factors, resulting in tumor resistance to therapy which only inhibits VEGF [25, 28].…”
Section: Discussionmentioning
confidence: 99%
“…Increased VEGF expression is related to tumor formation and progression [41]. A recent study of our research group showed that VEGF as well as the microvessel density increased in 8 to 18-week-old TRAMP mice in the prostatic tissue [26], assessed by CD31 immunoreactivity in endothelial cells. Similar findings were seen in the present study, which showed a progressive increase in VEGF and CD31 in the prostate of 8 to 22 week-old TRAMP mice.…”
Section: Discussionmentioning
confidence: 99%
“…Based on histological and immunohistochemical analysis, TRAMP mice tumors also showed high VEGF and FGF-2 expression, with increased microvessel density. Importantly, these mice recapitulate the stimulation of angiogenesis that has been observed in the aged mouse prostate, which is sensitive to treatment with antiangiogenic drugs (TNP-470 alone or in combination with SU5416) and finasteride (Montico et al 2014). The role of VEGF in advanced PCa has also been studied in Pten-conditional knockout mice.…”
Section: Mouse Models Of Pca and Relevant Aspects Of Angiogenesis/vegmentioning
confidence: 93%
“…The COX2, STAT3, IGFR1 and PCNA antigens were detected, respectively, using the following antibodies: mouse monoclonal anti-COX2 (sc-376861; Santa Cruz Biotechnology), rabbit polyclonal anti-STAT3 (sc-7179; Santa Cruz Biotechnology), rabbit polyclonal anti-IGFR1 (sc-712; Santa Cruz Biotechnology), and mouse monoclonal anti-PCNA (ab-29; Abcam). The pattern of protocols was the same as those described by Kido et al (2014) and Montico et al (2015) and all the primary antibodies were diluted in a 1:50 ratio, except for PCNA 1:250. Then, the sections were incubated for 2 h with HRP-conjugated secondary antibodies, goat anti-mouse IgG (W4021; Promega), and goat anti-rabbit IgG (W4018; Promega).…”
Section: Immunohistochemistrymentioning
confidence: 99%